Hypoxemia During Bronchoscopy and The Risk Factors Related - Putri, Chyntia Triana; Indriani, Sri Indah; Yovi, Indra (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: Hypoxemia, a common complication of bronchoscopy, often occurs even with oxygen supplementation, particularly during procedures performed under sedation, with reported incidences ranging from 2.5% to 69%. Hypoxemia during bronchoscopy which is defined as desaturation under 90% or more than 5% decreasing of basal SpO2, becomes a concern due to possible fatal complications. This study aims to determine the incidence of hypoxemia during bronchoscopy and identify its predisposing risk factors. Methods: An analytic observational study with a cross-sectional design was held in our center from October 2022 until June 2023. As many as 100 consecutive patients who underwent bronchoscopy and met inclusion criteria were evaluated prospectively. The patient’s oxygen saturation was monitored by finger pulse oximetry during the procedure. Demographic characteristics, comorbidities, lung function, PaO2 value, ASA score, types of intervention, sedative agents, duration of sedation and procedure were recorded. The risk factors for hypoxemia during bronchoscopy were evaluated. Results: The incidence of hypoxemia during bronchoscopy in our center was 15%. Bivariate analysis showed pleural effusion as a comorbidity (9 patients; 60%), restrictive-obstructive lung function test (10 patients; 66.7%) and PaO2 value (76.87±8.219) were statistically significant (P<0.05) related to the existence of hypoxemia during bronchoscopy. Three other factors such as age, ASA score and duration of procedure with P<0.25 were included in multivariate analysis and found that the most influencing factor was the restrictive-obstructive lung function test (P=0.001; OR=13.845). Conclusion: Comorbidity (pleural effusion), lung function (restrictive-obstructive) and PaO2 value were some factors significantly related to hypoxemia during bronchoscopy with lung function being the most influencing factor.